Concept of Wali Adlol Decision in Islamic and Positive Law Perspective - Mochamad Wahid Hasym (UNISKA LAW REVIEW, 2023)
Wedding is a vow between a man and a woman to reach the family goals. This definition strengthens that the wedding is like a vow that means there is freewill of each party to take the promise or having the similar principle of like or free contract in civil law. There are many problems aroused in the society, especially for the women who are ready to get married but sometimes complicated with the reluctant of her guardian to realize it. Finally, they take the simple way to realize their ambition and love by doing something avoided by the decency, obscenity, even religion norms. Therefore, the concept of adlol guardian decision in Islamic and positive law will be discussed in this research. This research used library research method whose a primary law source collection method is KHI and Islamic law source, either Al-Qoran or Al-Hadith, ijma’ and qiyas, while its secondary law sourceyis fiqh books or literature related to the problem. The result of research about the determination of adlol guardian in Islamic or positive law is as the following: there is khilafiah of the difference of opinion among some priests. Syafi’iyah and Malikiyah priests tells that if the guardian is reluctant or adlol, so the guardian’s duty will be directly taken by judge (Wali Hakim), while according to Hanafi and Hambali, it is forbidden to give the right of guardian to judge, but the right must be given to the following guardian by sequence till the end of the dzawil arham. While in Positive Law (KHI) in clause 23 verse 2 which tells if the guardian is reluctant or adlol, so the judge can be a guardian after court ruling. The positive law (KHI) should take all mahzab and change the guardian’s petition classified into volunteer at first to be contentious problem.